Notes on the impact on minors as a result of the use of unregulated reproduction techniques in Peru - Santome-Sánchez, Aldo Alesandro (2024)
Currently, in Peru we face numerous scenarios that are beyond the scope of our current regulations. An example of this is the case of assisted reproduction techniques, where the regulations are minimal and not very specific. This means that, in cases where these techniques are used, there is no proper regulation, causing multiple consequences and uncertainties. In this way, and given the legal loophole produced by the absence of a clear rule, many people who resort to these techniques to fulfill their wishes of becoming parents must employ various legal strategies to regularize the situation of minors born through their use, from maternity impugnation processes to adoption judicial processes. This often results in prolonged judicial litigation that affects several fundamental rights of minors, such as the right to know their biological truth, the right to have a stable family, and the right to comprehensive well-being.